The Juridical Sociological Review of Zakat Fitrah Distribution in Pomalaa Subdistrict, Kolaka Regency - Chasanah, Rosda; sari, Patma; Muhammad As Ari. AM; Yeni Haerani; Irabiah; Ernita Ramadhani bym; Faisal Herisetiawan Jafar (Jurnal Hukum Volkgeist, 2024)
This research aims to examine and analyze the Sociological Juridical Review of Zakat Fitra Distribution in Pomalaa District, Kolaka Regency. The analysis technique in this research uses qualitative analysis techniques. Provisions for the Distribution of Zakat Fitrah must be distributed immediately to mustahik for 8 groups (asnaf), poor people, poor people, those who have softened their hearts (converts), to (free) servants, to (free) people who donate, filsabilillah and for people who are on a journey, as Allah says in the Qur'an surah at-Taubah 60. If you have not had time to pay zakat fitrah before the Eid al-Fitr holiday, it is sunnah to pay zakat after the morning prayer before the Eid al-Fitr prayer. The makruh time to pay zakat is after Eid al-Fitr and before sunset on Hari Raya. Even though this time is considered quite risky, it is still recommended to pay zakat fitrah at this time if Muslims have not had the opportunity to do it before, so that no Muslims go hungry on Eid al-Fitr. Delays in the distribution of zakat fitrah in the district. Pomalaa in Kab. Kolaka at the Nurul Huda Mosque is due to the awareness of the community in collecting zakat and the zakat distribution committee which is a new form of youth during the month of Ramadhan, which always changes every year and does not understand and does not review the provisions of zakat fitrah so that the community receiving zakat fitrah does not receive zakat. Accordingly, the distribution of zakat becomes uneven.